(untitled) (Research, Society and Development, 2024)
The aim of this article is to analyze the efficiency and highlight possible pathological manifestations apparent in four bridges comprising reinforced concrete and metal structures, located in the Vila Ildemar neighborhood in the municipality of Açailândia, Maranhão State (MA), Brazil. The research makes a detailed investigation of possible failures and damages identified in the structures through a case study, with a special emphasis on the identification and characterization of pathological manifestations. In addition, it evaluates the structural efficiency of the pontoons, by means of visual technical analysis and ultrasonic testing, highlighting aspects related to the quality and integrity of the pontoons and their performance in general, bringing to light the factors that may be causing the problems, providing valuable information for public managers and others interested in preserving and improving the local road infrastructure. Based on the results obtained, we can demonstrate possible solutions and improvements to mitigate and prevent future problems, as well as showing the quality of the concrete as a function of the speed of propagation of the ultrasonic wave, according to the data obtained in the test.